Transformasi Kisah Nabi Khidir: Kajian Historis dan Tekstual atas Narasi Al-Qur’an dan Sastra Suluk Sufistik Nusantara - Rusmana, Dadan; Nurjaman, Ilham Muhamad; Ilham, Ilham; Kusmardani, Alex (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2025)
This article examines the transformation of the story of Prophet Khidir from its Qur'anic narrative into Sufi literary expressions known as Serat Suluk in the Indonesian archipelago. The study focuses on the processes of spiritual reinterpretation and cultural recontextualization undertaken by local Sufi scholars in reshaping the character of Khidir to align with the mystical and cultural values of Javanese Islam. Employing historical research methods—including heuristics, source criticism, interpretation, and historiography—this study utilizes the theory of text transformation as its main analytical framework. The findings reveal that Sufi writers in the Nusantara did not alter the theological substance of Khidir’s story but constructed new narratives featuring localized mystical symbols and figures such as Sunan Kalijaga and Syekh Malaya. These figures function as seekers of divine knowledge and mystical insight under Khidir’s spiritual guidance. Such transformations reflect the adaptability of religious texts to local cultural contexts while preserving their core ethical and theological messages. Keywords: Prophet Khidir; Textual transformation; Sufi suluk; Islam Nusantara; Religious literature